The impact of laser radiation on nanoparticles, which using in medical - Obozna, V. P.; Hnatenko, O. S. (Sumy State University, 2019)
This paper proposes a method of modified chemotherapy, which consists in the use of nanoparticles of porous silicon. These pores are filled with medicine for chemotherapy.
Keywords: nanoparticles; laser; porous silicon